The role of the school when a family crisis takes place. (Journal of Parents and Teachers, 2014)
Crises in families are becoming more frequent, and because the school has the mission of educating students personally and academically, it must help them to cope with these moments of family crisis.
Keywords: Family crisis; college; helping to deal with problems.